Peran Guru PAI dalam Menanamkan Nilai-Nilai Multikultural Ditinjau dari Indikator Keterlaksanaan Beny Susetyo - Jannah, Riadhotul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
As an effort to develop a perfect human being, Islamic education is required to be able to make people aware of plurality and diversity. Because awareness of plurality is the beginning of building multicultural attitudes and behaviors. The problems posed in this study include the following questions: 1) What is the role of PAI teachers in instilling multicultural values ​​in students at SMAN 4 Kediri City? 2). How is the role of PAI teachers in terms of implementation indicators (Beny Susetyo) in instilling multicultural values ​​in students at SMAN 4 Kediri City?. With the research objectives, namely; 1). To identify how the role of PAI teachers in instilling multicultural values ​​in students at SMAN 4 Kediri City. 2). To identify how the role of PAI teachers in terms of implementation indicators (Beny Susetyo) in instilling multicultural values ​​in students at SMAN 4 Kediri City?. This study uses a descriptive qualitative approach with data collection techniques through interviews and documentation. Based on the results of the study, it can be concluded that: 1) PAI teachers at SMAN 4 Kediri City play an active role in instilling multicultural values ​​in each lesson through a contributions approach and an aditif approach 2). PAI teachers at SMAN 4 Kediri have a role in carrying out the inculcation of multicultural values ​​such as tolerance values, democratic values, and humanism values ​​in the form of mutual respect, being patient, not selfish, and not forcing the opinions of others.